Aortic Dysfunction in Mitral Regurgitation Due to Floppy Mitral Valve/Mitral Valve Prolapse - Mowafy, Hatem; Lilly, Scott; Orsinelli, David A.; Rushing, Gregory; Crestanello, Juan; Boudoulas, Konstantinos Dean (AORTA, 2018)
Background Floppy mitral valve/mitral valve prolapse (FMV/MVP), a heritable disorder of connective tissue, often leads to mitral regurgitation (MR) and is the most common cause for mitral valve surgery in developed countries. Connective tissue disorders may affect aortic function, and a stiff aorta may increase the severity of MR. Aortic function, however, has not been studied in FMV/MVP with MR.Methods A total of 17 patients (11 men, 6 women) with FMV/MVP and significant MR were compared with 20 controls matched for age and gender. Aortic diameters (AoD) were measured from left ventriculograms at 2 and 4 cm above the aortic valve. Aortic pressures were measured directly using fluid-filled catheters. Aortic distensibility was calculated using the formula: 2(systolic AoD—diastolic AoD)/(diastolic AoD x pulse pressure).Results Aortic distensibility was significantly lower in FMV/MVP compared with control at 2 cm above the aortic valve (1.00 ± 0.19 versus 3.78 ± 1.10 10−3 mm Hg−1, respectively; p = 0.027) and 4 cm above the aortic valve (0.89 ± 0.16 versus 3.22 ± 0.19 10−3 mm Hg−1, respectively; p = 0.007). FMV/MVP patients had greater left ventricular (LV) end-systolic (88 ± 72 mL versus 35 ± 15 mL, p = 0.002) and end-diastolic (165 ± 89 mL versus 100 ± 41 mL, p = 0.005) volumes, and lower LV ejection fraction, compared with control (50 ± 12% versus 57 ± 6%, p = 0.034).Conclusion Aortic distensibility is decreased (consistent with a stiff aorta) in patients with FMV/MVP and MR. A stiff aorta may increase the severity of MR. Thus, abnormal aortic function, which also deteriorates with age, may play an important role in the natural history of MR due to FMV/MVP.
Keywords: floppy mitral valve; mitral valve prolapse; aorta; distensibility